Impact of alternative diagnostic labels for melanoma in situ on management choices and psychological outcomes: protocol for an online randomised study - Brooke Nickel; Lisa Parker; Jon Emery; Richard A Scolyer; Raymond Barnhill; David Elder; Katy JL Bell; Elspeth Davies; Blake O'Brien; Adewole S Adamson; Alexander C J van Akkooi; Farzaneh Boroumand; et al. (BMJ Open)
Introduction A diagnosis of melanoma in situ presents negligible risk to a person’s lifespan or physical well-being, but existing terminology makes it difficult for patients to distinguish these from higher risk invasive melanomas. This study aims to explore whether using an alternative label for melanoma in situ may influence patients’ management choices and anxiety levels.Methods and analysis This study is a between-subjects randomised online experiment, using hypothetical scenarios. Following consent, eligible participants will be randomised 1:1:1 to three labels: ‘melanoma in situ’ (control), ‘low-risk melanocytic neoplasm’ (intervention 1) and ‘low-risk melanocytic neoplasm, in situ’ (intervention 2). The required sample size is 1668 people. The co-primary outcomes are (1) choice between no further surgery or further surgery to ensure clear histological margins greater than 5 mm and (2) choice between patient-initiated clinical follow-up when needed (patient-led surveillance) and regular routinely scheduled clinical follow-up (clinician-led surveillance). Secondary outcomes include diagnosis anxiety, perceived risk of invasive melanoma and of dying from melanoma and management choice anxiety (after surgery choice and follow-up choice). We will make pairwise comparisons across the three diagnostic label groups using regression models (univariable and multivariable).Ethics and dissemination The study has been registered with the Australian New Zealand Clinical Trials Registry (ACTRN12624000740594). Ethics approval has been received from The University of Sydney Human Research Ethics Committee (2024/HE000019). The results of the study will be published in a peer-reviewed medical journal, and a plain language summary of the findings will be shared on the Wiser Healthcare publication page (https://www.wiserhealthcare.org.au/category/publications/).Trial registration number Australian New Zealand Clinical Trials Registry (ID 386943).